Leadership in standard chartered organization: a comparative study between Malaysia and Japan / Raja Alia Zafirah Raja Abdul Rahim - Raja Abdul Rahim, Raja Alia Zafirah (2012)
Leadership literature in the past decade has drawn a sharp distinction between three types of leadership: transactional, charismatic and transformational. The leadership has dealt extensively with the sources and aspects of these leadership patterns, particularly in the context of “the leader and his people”. Hence this paper will look through in comprehensive view and examines the probability of the various leadership patterns emerging in organizations from the point of view of the conditions prevailing in the organization and their psychological implications. The dilemma faced by many businesses today is managing strategic change initiatives efficiently and effectively. Arguably, managing changes simultaneously poses great challenges to organizational success in terms of the desired change. The purpose of this paper is to discuss the driving forces that occurred during management of change in Standard Chartered bank in two countries that are Malaysia and Japan. Issues in the implementation process include change initiatives and the challenges that were faced by the leaders. This observation suggests that organizational leaders should give careful attention to how each activity can be designed and well integrated when planning and implementing organizational change in order to succeed.